2002
DOI: 10.1097/00005768-200209000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual versus physiological heat strain during exercise-heat stress

Abstract: T underestimated and U consistently perceived their physiological strain, as defined by PhSI, in accordance with the measured increases in core temperature and heart rate throughout an exposure to uncompensable exercise-heat stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
121
3
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(134 citation statements)
references
References 24 publications
9
121
3
1
Order By: Relevance
“…This value closely resembled the heart rate observed at the end of the simulated fire task reported by von Heimburg 75 and the heaviest of works tasks used by Holmer and Gavhed. 29 Body core temperatures from the present investigation ranged from 37.04 to 38.53°C and are similar to those reported by Moran et al 50 when developing the physiological heat strain index (37.12 to 38.7°C) and by Tikuisis et al 70 when developing the perceptual heat strain index (37.1 to 38.3°C). The four interrelated experimental paradigms employed presently resulted in a range of body core temperatures sufficient for the development of the perceptual hyperthermia index (PHI).…”
Section: Physiological Responsessupporting
confidence: 89%
See 3 more Smart Citations
“…This value closely resembled the heart rate observed at the end of the simulated fire task reported by von Heimburg 75 and the heaviest of works tasks used by Holmer and Gavhed. 29 Body core temperatures from the present investigation ranged from 37.04 to 38.53°C and are similar to those reported by Moran et al 50 when developing the physiological heat strain index (37.12 to 38.7°C) and by Tikuisis et al 70 when developing the perceptual heat strain index (37.1 to 38.3°C). The four interrelated experimental paradigms employed presently resulted in a range of body core temperatures sufficient for the development of the perceptual hyperthermia index (PHI).…”
Section: Physiological Responsessupporting
confidence: 89%
“…Hoster et al 31 reported PeSI was significantly greater than PhSI after 8-mins, 23-mins, and at termination of treadmill exercise for subjects wearing personal protective equipment. Tikuisis et al 70 62 Additionally, in the present investigation PhSI and…”
Section: Relation Between Physiological and Perceptual Responsessupporting
confidence: 57%
See 2 more Smart Citations
“…에 의해 제안된 식을 조금 수정한 Tikuisis et al (22) 의 식을 사용했으며, 계 산식은 다음과 같다; PhSI는 안정 시 1.2 ± 0.6이었으나, 첫 번째, 두 번째, 세 번째 세트를 완료한 직후의 PhSI는 각각 4.6 ± 0.5, 6.1 ± 1.0, 7.6 ± 1.2이었다. 60분 간의 회복 후 PhSI는 2.6 ± 0.8 이었다( Figure 2D).…”
Section: 소방관 체력검정unclassified